Comparative epidemiology and virology of fatal and nonfatal cases of hand, foot and mouth disease in mainland China from 2008 to 2014. (20th February 2015) - Liu, She‐Lan; Pan, Hao; Liu, Peng; Amer, Said; Chan, Ta‐Chien; Zhan, Jun; Huo, Xixiang; Liu, Yunzhi; Teng, Zheng; Wang, Ling; Zhuang, Hui
Summary This study aimed to analyze the epidemiology and virology of fatal and nonfatal hand, foot, and mouth disease (HFMD) cases in Mainland China. A total of 10 714 237 survivors and 3046 deaths were reported from 2008 to 2014 June, with a case fatality rate of 0.03%. The morbidity of the survivors increased from 37.6/100 000 in 2008 to 139.6/100 000 in 2013 and peaked in 2012 at 166.8/100 000. However, the mortality varied around 0.03–0.04/100 000 across the time. Most of the survivors were distributed in the southern and eastern China, predominantly in the Guangxi and Hainan Province, whereas deaths were dominant in southern (Guangxi) and southwestern (Guizhou) China. The two groups showed similar seasonal fluctuations from 2008 to 2014, peaking in spring and early summer. Of the total cases, 93.97% were children less than 5 years of age, with those ≤ 2 years old accounting for 60.08% versus 84.02% in the survivor and death groups, respectively. Boys were at higher risk of infection than girls in both groups. Five years of virological surveillance showed that 43.73%, 22.04%, and 34.22% of HFMD cases were due to EV71, CoxA16 and other enteroviruses, respectively. EV71 was encountered in most deaths, with no substantial effect of age, gender, month, and year on incidence. Subgenotype C4a was the prevalent EV71 strain in Mainland China, with no significant difference in the VP1 gene related to virulence between the two groups. In conclusion, based on the largest population study, fatal and nonfatal HFMD cases, mainly caused by C4a of EV71, are circulating in Mainland China with a low‐cause fatality rate. Copyright © 2015 John Wiley & Sons, Ltd.